Promosi Manajemen Kesehatan Jiwa - Puput Mulyono; Singgih Purnomo (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Mental health problems in teenagers are often not detected from the start. This is because many parents and teenagers are reluctant to seek professional mental health services. The method used is to provide health education and distribute material in the form of leaflets via WhatsApp which contains information about how to manage emotions well. Mental health management is all planning and control efforts. necessary to express all emotions. Promotion of mental health can be carried out on an ongoing basis for adolescents as an effort to maintain mental health and prevent the risk of psychosocial problems emerging in adolescents.